ANALYSIS OF THE FACTORS THAT INFLUENCE CUSTOMER INTEREST IN USING MOBILE BANKING AT PT. BANK NTB SYARIAH ALAS SUB-BRANCH - Sandy, Agusta Hari; Hermanto, Koko (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Many customers prefer ATMs or come directly to bank offices to do banking transactions. It can lead to crowds considering that the pandemic is not over yet. It is one of the considerations of PT. Bank NTB Syariah launched a mobile banking application as a service facility to facilitate customers' transacting. The use of mobile banking is still relatively new to the public. Currently, the number of mobile banking users of Bank NTB Syariah Alas Sub-Branch has not met the number of targets achieved in several quarters. This study aimed to analyze the factors influencing customer interest in mobile banking. The sample in this study amounted to 100, which are customers who are users of mobile banking users of PT. Bank NTB Syariah Alas Sub-Branch. The statistical tool used in this research is Structural Equation Modeling (SEM) with LISREL 8.80 statistical software approach. The results of this study indicate that the factors that influence customer interest are Perception of Information Technology (X1), Ease of Use (X2), Risk (X3), and Service Features (X4). These factors have a significant simultaneous effect. The coefficient of determination obtained is 84%, which means that customer interest in using mobile banking is influenced by elements of information technology perception, risk, trust, and service features, while the remaining 16% is influenced by other variables not discussed in this study.